PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU MADRASAH DI MADRASAH IBTIDAIYAH MIFTAHUL HUDA MALANG - Rizki Cahyaning Arifin Putri; Azhar Haq; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The research conducted is about the role of the headmaster in improving the quality of madrasah in the Madrasah Ibtidaiyah Miftahul Huda Malang. The research method used is qualitative research. Data collection techniques used were observation, interviews and documentation. In this study, researchers found the role of the headmaster and factors supporting and inhibiting headmaster in improving the quality of the headmaster. The role of the madrasah head is by holding the leadership principle Qawwiyun Aminun, as well as the role of leader, role as manager and role as educator. In carrying out all of these roles, there are factors supporting and inhibiting madrasah principals in improving the quality of madrasas, among other factors supporting principals in the role of teachers and student guardians. increasingly tight agendas in madrasas over the last five years, as well as the high desire and expectations of teachers and employees for madrasah progress as the inhibiting factor is the minimal school land owned by madrasas so that classrooms are still very limited, in terms of infrastructure has been fulfilled but it is still very limited, the lack of collaboration between teachers and employees in the team when procuring school programs.